Associations of self-reported vision problems with health and psychosocial functioning: a 9-year longitudinal perspective - Wettstein, Markus; Spuling, Svenja M.; Wahl, Hans-Werner; Heyl, Vera (British journal of visual impairment, 2021)
However, little is known about how impaired vision affects the long-term trajectories of these outcomes, whether effects are moderated by age, and whether psychosocial resources beyond well-being such as subjective age views are also affected by vision loss. We analyzed how self-reported vision problems as a time-varying predictor are related to long-term changes in health and cognitive ability (functional health, number of chronic diseases, self-rated health, information processing speed), well-being (life satisfaction, positive and negative affect, depressive symptoms, loneliness), and subjective age views (subjective age; aging-related cognitions: social loss, physical decline, continuous growth). Our sample was derived from the German Ageing Survey, comprising 6,378 individuals (40–89 years) who provided up to four observations over a 9-year period. Controlling for gender, age, education, and functional as well as self-rated health, we observed that both on a between- and a within-person level, indicators of successful aging were consistently less favorable among individuals with more vision problems. Associations between vision problems and functional health became stronger with advancing age. In contrast, with increasing age, vision problems were less closely associated with change in several indicators of psychosocial functioning. Our findings suggest that self-reported visual impairment is associated with restrictions across a broad range of developmental domains. Some detrimental effects of vision problems are augmented in later life, whereas several effects on well-being and subjective age views were attenuated with advancing age, which might indicate processes of late-life adaptation to vision loss.
Gesehen am 13.11.2020